2021
DOI: 10.1002/jpen.2265
|View full text |Cite
|
Sign up to set email alerts
|

Normal anthropometry does not equal normal body composition in pediatric intestinal failure

Abstract: Background Published reports on abnormal body composition in pediatric patients with intestinal failure have been in patients with poor growth. The goal of the current study is to report the body composition of normally growing patients with intestinal failure. Methods Children 8–18 years old with a dual‐energy x‐ray absorptiometry (DXA) between January 1, 2013, and July 15, 2018, were included in the study. Data were retrospectively collected from the medical charts and included demographics, residual bowel a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 45 publications
3
18
1
Order By: Relevance
“…26 Children with intestinal failure receiving parenteral nutrition have been reported to have reduced physical activity 27,28 and lower lean mass despite similar body weight compared with their peers. 21,[28][29][30] Additional research in this area is needed to optimize the bone health of children with intestinal failure.…”
Section: Bmd Results By Age Group Are Shown In Tablementioning
confidence: 99%
See 1 more Smart Citation
“…26 Children with intestinal failure receiving parenteral nutrition have been reported to have reduced physical activity 27,28 and lower lean mass despite similar body weight compared with their peers. 21,[28][29][30] Additional research in this area is needed to optimize the bone health of children with intestinal failure.…”
Section: Bmd Results By Age Group Are Shown In Tablementioning
confidence: 99%
“…Unfortunately, we did not have information on bone loading physical activity or lean body mass, both of which are positively associated with BMD in children 26 . Children with intestinal failure receiving parenteral nutrition have been reported to have reduced physical activity 27,28 and lower lean mass despite similar body weight compared with their peers 21,28–30 . Additional research in this area is needed to optimize the bone health of children with intestinal failure.…”
Section: Discussionmentioning
confidence: 99%
“…Despite normal anthropometry, body composition may be abnormal in SBS children (25). In infants with IF requiring PN after intestinal surgery, poor body weight gain was associated with poor fat mass gain, while fat free mass was adequate (26).…”
Section: Aim Of Treatmentmentioning
confidence: 99%
“…However, studies in older children have reported increased adiposity and reduced lean body mass SBS resulting in an apparently correct BMI in children with a higher fat mass (25,27,28). Dual X-ray absorptiometry (DXA), routinely used in SBS children since they are at risk of low mineral bone density (see below), may be an adequate method to assess body composition (25,29), however other routine methods avoiding X-ray radiation may be considered.…”
Section: Nutritional Statusmentioning
confidence: 99%
“…Studies have shown that children with IF and dependence on PN may have abnormal body composition (BC) with lower levels of lean or fat-free mass (FFM) and higher levels of fat mass (FM) (7)(8)(9). In addition, they may be at risk for disease or nutrition-related sarcopenia, defined as reduced muscle strength accompanied by loss of skeletal muscle mass and/or and low physical performance (10).…”
mentioning
confidence: 99%